Kajian terhadap Sarana Duduk Publik Kampus dengan Pendekatan Perilaku dan Aktivitas Warga Kampus (Studi Kasus pada Kampus Institut Teknologi Bandung Ganesha) - Arianti Ayu Puspita; Dudy Wiyancoko; Dona Saphiranti (ITB Journal Publisher, LPPM ITB, 2013)
This research is motivated by a number of outdoor public furniture, which is not functional, not in place and even unused. The expected result is the discovery of a tendency of design criteria to sit to meet the needs of students.